Softening dynamics of polymer blends and composites investigated by differentia spectra of dynamic mechanical analysis. Issue 7 (11th December 2017) - Zhang, Rui; He, Xianru; Rodrigues, Alisson M.; Guo, Qipeng
Abstract: The confinement effect on molecular motions has been widely observed in polymeric blends and composites. For polymers that have softening dynamics in glass–rubber transition region, the confinement effect can influence the molecular motions to different degrees. In this work, the differentia spectra of dynamic mechanical analysis were applied to analyze the confinement effect in butyl rubber (IIR)/ethylene‐vinyl acetate copolymer (EVA) blends, IIR/high‐density polyethylene (HDPE) blends, chlorobutyl rubber (CIIR)/polystyrene (PS) blends, IIR/silica composites, and CIIR/organophilic montmorillonite (OMMT) composites. In the differentia spectra, the confinement effect from additional components on local segment motions (LSM), sub‐Rouse modes, and Rouse modes was investigated, indicating that the effect on sub‐Rouse modes is smaller than that on Rouse modes but larger than that on LSM. Moreover, the coupling effects slightly change with introduction of the secondary components, which enables us to assume that the confinement effect has a linear relationship with the content of secondary components. Finally, it has been found that the decrease in tan δ exhibited a linear relationship with the content of secondary components.